Early Outcome of Patient Born with Gastroschisis and Omphalocele - Berdawd, Salar S.; Taha, Abdulrahman O. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Gastroschisis and omphalocele are the most common congenital defects of the anterior abdominal wall which need urgent and prompt intervention post-operative time outcomes of gastroschisis and omphalocele differ between different countries, especially between developed and developing countries. Objectives: Is to determine the early outcome of patients born with gastroschisis and omomphalocele Patients and Methods: An analytical study including 30 patients (11 gastroschisis and 19 omphaloceles) were treated in Erbil city during 2015 -2018. Patients with associated bladder and cloacal exstrophies were excluded. Results: Female to male ratio was 1.3:1, and the mean age at presentation was 11.7 hours. The Mean weight was 2.86 kg. the Majority of patients25 (83.3%) were term. In Nineteen cases (63.3%)were delivered vaginally (9 gastroschisis and 10comphalocele), prenatally diagnosis was done in 9(30%). The Mean size of the defect was 3.7cm, and the content was mixed in 7(23.3%). Primary repair has performed in 18(60%), a silo in 8(26.7%), and 4(13.3%) treated none surgically (all were omphalocele). Operations have been done within 24 hours of arrival in 16(61.5%). Associated anomalies have been found in 11(57.9%) patients with omphaloceles and only 2(18.2%) patients with gastroschisis. The mean period of hospital stays was6 days. Mortality among the gastroschisis patients were 8(72%), but only 4(21.1%) for omphalocele patients. Conclusion: Gastrochisis and omphalocele constitute a considerable part of neonatal surgical problems and their management is still challenging. Omphalocele cases were more likely to have associated congenital anomalies and gastroschisis, if the associated anomalies were confined to the gastrointestinal tract. There was a high mortality rate, especially in patients with gastroschisis and ruptured omphalocele due to a lack of intensive care units, facilities, and trained personnel to look after such high-risk patients.